Book of Hours Geofroy Tory, Spirit Renaisans dalam Kontinuitas Ide Desain - Fitro Nur Hakim - STMIK Provisi Semarang (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
Abstract: Graphic design work is widely known in commercial products, such as print ads, televisionand internet. Beginning with the application of engineering design and technology actually beganduring the Renaissance. Media distribution of graphic design has undergone a major evolution.Analysis of the work